A study of age effect through NDT and crushing strength of concrete with different industrial wastes under loading and unloading conditions. (2021) - Paktiawal, Ajmal; Alam, Mehtab
Abstract: The strength of concrete is affected by several factors, such as water to binder ratio, quality and the ratio of coarse to fine aggregates, ambient temperature, method of curing, and curing age. This research work aims to study the impact of curing age on NDT and crushing strength of concrete with different industrial wastes under loaded and unloaded conditions. Three different types of wastes were utilized in high-strength concrete, grade M60. In the first mix, the fine aggregate was substituted by the crushed waste glass with various percentages of 0, 10, 20, 30, and 40 by weight. In the second mix, the cement was substituted by aluminum waste with different percentages of 0, 2, 4, 7, and 12%, and LDPE was added by weight of cement with 3.5, 7, 12.5, and 21%. To study the role and effect of LDPE waste only on strength of concrete and NDT results, the third mix LDPE with varying percentages of 0, 3.5, 7, 12.5, and 21 was added by cement weight. A precise experimental program was conducted to investigate the response of specimens by applying ultrasonic pulse velocity and surface hardness under unloaded conditions and loading conditions with 25% of the ultimate crushing strength. The findings of unloaded and loaded conditions for UPV and surface hardness found from concrete specimens of various waste at stipulated ages have been associated with their compressive strength. Increased surface hardness and pulse velocity test results of the concrete with varying substitution levels of the wastes after 210 and 270 days of curing are discussed. It was found that the industrial wastes used in this study with different substitution levels reduce the ultrasonic pulse velocity under unloading conditions at the age of 28, 210, and 270 days. The findings related to UPV and surface hardness for all type of wastes under loaded conditions are found lower than that of unloading conditions.